2020
DOI: 10.1093/police/paaa052
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Police Sexual Misconduct in the UK

Abstract: Sexual misconduct in police officers and staff is a serious form of corruption with negative consequences for victims and the reputation of the police. It can include a variety of behaviours ranging from inappropriate sexual comments to colleagues to sexual activity with vulnerable victims of crime. Analysis of publicly accessible data available from proven cases of sexual misconduct in 30 police forces in England and Wales has identified eight categories of sexual misconduct, together with the subsequent disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…The survey comprised eight scenarios, written to include a range of sexual misconduct types demonstrated by UK police officers, as found by Sweeting et al (2021). To ensure the scenarios were realistic, each was based loosely on a real-life incident of sexual misconduct encountered by the first author during her service as a police officer.…”
Section: Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey comprised eight scenarios, written to include a range of sexual misconduct types demonstrated by UK police officers, as found by Sweeting et al (2021). To ensure the scenarios were realistic, each was based loosely on a real-life incident of sexual misconduct encountered by the first author during her service as a police officer.…”
Section: Scenariosmentioning
confidence: 99%
“…The sexualised nature of his comments could also constitute sexual misconduct and sexual harassment (Maher, 2003; Zhu et al, 2019). This type of colleague-on-colleague sexual misconduct was found to account for 21.9% of a recent sample of police sexual misconduct cases (Sweeting et al, 2021). Another type of sexual misconduct, termed abuse of position for a sexual purpose, in which officers engage in sexual or improper emotional relationships with vulnerable members of the public, is currently a national priority for research (NPCC, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A couple of decades later, Page (2007) reported that rape myth acceptance existed among officers from 11 agencies in the Southeastern USA, but at much lower rates. Considering the cultural beliefs toward rape victims held by some in law enforcement, it comes as no surprise that officer sexual abuse incidents are often perpetrated against individuals of marginalized status who are especially vulnerable to police powers, including sex workers (Barker, 2020;Cottler et al, 2014), juveniles (Stinson et al, 2015;Walker and Irlbeck, 2003) and even fellow officers in lower ranks (Martin, 1980(Martin, , 1989(Martin, , 1990Sweeting et al, 2021Sweeting et al, , 2022.…”
Section: Sexual Misconduct In Law Enforcementmentioning
confidence: 99%
“…While much of the PSM literature is becoming dated (Barker, 1978; Sapp, 1986), more current examinations continue to find the same associated characteristics, realities and trends (Barker, 2020; Silvestri, 2017; Stinson et al. , 2020; Sweeting et al. , 2021, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation